2015
DOI: 10.1002/tkm2.1023
|View full text |Cite
|
Sign up to set email alerts
|

Quick and easy preparation method for decoction of Kampo formula inspired by the method of boiling powdered crude drugs in the Song period of China

Abstract: Aim:For the purpose of reducing both the consumption of crude drug resources and patient burden in preparing the decoctions, we developed a new preparation method for the decoctions of Kampo formula: immersion of powdered crude drugs in hot water (IPCD method), inspired by a method of decoction that was widely used in the Song period of China. Methods: Ephedra herb (terrestrial stem of Ephedra sinica), scutellaria root (root of Scutellaria baicalensis), and Kampo formulas that contain several crude drugs inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…The IPCD method was developed for easier preparation of Kampo decoctions. In the IPCD method, the crude drugs are powdered and mixed vigorously with boiled water then filtered after 4 min [ 11 ]. This method is convenient; however, the short heating time results in intense residual acridity of the unprocessed Pinellia Tuber, which is a major problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IPCD method was developed for easier preparation of Kampo decoctions. In the IPCD method, the crude drugs are powdered and mixed vigorously with boiled water then filtered after 4 min [ 11 ]. This method is convenient; however, the short heating time results in intense residual acridity of the unprocessed Pinellia Tuber, which is a major problem.…”
Section: Discussionmentioning
confidence: 99%
“…Hangekoubokuto (banxiahoupotang) immersion was prepared using the immersion of powdered crude drugs (IPCD) method [ 11 ]. Pinellia Tuber (6.0 g), Poria (5.0 g), Magnolia Bark (3.0 g), Perillae Herba (2.0 g), and dried Ginger (1.0 g) were mixed and milled for 1 min.…”
Section: Methodsmentioning
confidence: 99%
“…When unprocessed aconite root was extracted using purified water, the amount of diester alkaloids in the IPCD immersion was approximately ninefold that in the conventional decoction. The ratio of the increase was much larger than that for the non‐volatile marker compounds of crude drugs previously reported . Also, the amount of benzoylemesaconine, the hydrolysate of mesaconitine, was significantly lower in the IPCD immersion compared with conventional decoction.…”
Section: Discussionmentioning
confidence: 54%
“…We developed the immersing powdered crude drugs (IPCD) method with a view to shortening the preparation time. We have already shown that even better extraction efficiency is obtained within only 4 min of easy incubation in the IPCD method than by 30 min of conventional decoction . It has been said, however, that 30 min of boiling is required not only for good extraction efficiency but also to reduce the toxicity of crude drugs with strong physiological activity .…”
Section: Introductionmentioning
confidence: 99%
“…As reported before, we have developed a new method of preparing decoctions by immersing powdered crude drugs in hot water without boiling, named the immersing powdered crude drugs (IPCD) method. Despite its quickness, the extraction efficiency of IPCD is slightly higher than that of the conventional decoction method and as a result of the shorter period of heat, a higher efficiency is expected with regard to the volatile compounds from crude drugs. In this study, the decoctions made from cinnamon bark and perilla herb using the IPCD method were more than twice as rich in the volatile marker compounds compared with conventional decoctions.…”
Section: Introductionmentioning
confidence: 99%